2020
DOI: 10.1039/c9ra07803g
|View full text |Cite
|
Sign up to set email alerts
|

R-VAPOL-phosphoric acid based1H and13C-NMR for sensing of chiral amines and acids

Abstract: R-VAPOL-chiral solvating agent for discrimination of chiral amines and acids using 1H and 13C NMR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…In the 1 H NMR spectra of silver­(I) complexes with chiral L ligands, two sets of doublets for methyl protons from the two diastereomers were observed. , By contrast, ( S )- L 1 showed one doublet for the methyl protons, which indicated that diastereomers did not form.…”
Section: Resultsmentioning
confidence: 96%
“…In the 1 H NMR spectra of silver­(I) complexes with chiral L ligands, two sets of doublets for methyl protons from the two diastereomers were observed. , By contrast, ( S )- L 1 showed one doublet for the methyl protons, which indicated that diastereomers did not form.…”
Section: Resultsmentioning
confidence: 96%
“…Enantiopurity of amino alcohols is important in this context as (S)-propranolol is an active beta-blocker, whereas the (R)-isomer is ineffective in this application but has utility as a potential contraceptive. [24] A universal noncovalent chiral shift reagent for the determination of relative configuration by NMR spectroscopy does not exist and the chiral recognition of amino alcohols has been achieved using several chiral shift reagents, including arylcarboxylic acids, [25][26][27] atropisomers, [28] calixarenes/ resorcinarenes, [29][30][31][32][33][34][35][36] cyclodextrins, [37] crown ethers, [38][39][40] phosphorous-containing reagents, [41][42][43][44] and metallocomplexes, [45,46] amongst others. [47][48][49][50] The separation of amino alcohols has been almost exclusively limited to organic solvents except for resorcinarene and cyclodextrin hosts which have displayed separation in aqueous media.…”
Section: Application Of {Mo 132 (Lactate) 30 } Structures As Chiral Shift Reagentsmentioning
confidence: 99%
“…The determination of enantiopurity via NMR spectroscopy required the presence of a chiral auxiliary to convert the enantiomers into diastereomers. The most commonly used chiral auxiliaries are chiral solvating agents {CSAs like tyrosine-modied pillar [5] arenes, R-VAPOL-phosphoric acid, organic-soluble acids, benzene tricarboxamide-based hydrogelators, BINOL phosphoric acid, Kagan's amides, roof-shape amines, BINOL and its derivatives}, [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] chiral derivatizing agents {CDAs like D-[Ir(ppy) 2 (MeCN) 2 ](PF 6 ) (ppy is 2-phenylpyridine), a-methoxy-aphenylacetic acid (MPA), a-methoxy-a-triuoromethylphenylacetic acid (MTPA) and BINOL}, [31][32][33][34][35][36] chiral lanthanide shi reagents {CLSRs like [Eu(tfc) 3 ], [Eu(hfc) 3 ], [Sm(tfc) 3 ], and [(R)-Pr(tfc) 3 ]}. [37][38][39] Among all the chiral auxiliaries reported for NMR chiral recognition, BINOL and its derivatives represent a useful auxiliary because of their direct utilization as a CSA.…”
Section: Introductionmentioning
confidence: 99%